1984
DOI: 10.1172/jci111336
|View full text |Cite
|
Sign up to set email alerts
|

Impaired formation of beta-adrenergic receptor-nucleotide regulatory protein complexes in pseudohypoparathyroidism.

Abstract: Abstract. Decreased activity ofthe guanine nucleotide regulatory protein (N) of the adenylate cyclase system is present in cell membranes ofsome patients with pseudohypoparathyrodism (PHP-Ia) whereas others have normal activity of N (PHP-Ib). Low N activity in PHPIa results in a decrease in hormone (H)-stimulatable adenylate cyclase in various tissues, which might be due to decreased ability to form an agonist-specific high affinity complex composed of H, receptor (R), and N. To test this hypothesis, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 32 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Biochemical assays that measure hormone signaling after reconstitution of patient cell membranes with membranes that totally lack G s (cycϪ) demonstrated that in PHPIA functional G s activity is decreased by approximately 50% in membranes from various cell types, including erythrocytes, fibroblasts, platelets, lymphocytes, and kidney (288,(325)(326)(327)(328)(329)(330)(331)(332)(333)(334)(335). Functional studies in membranes (304,338) and whole cells (339) confirmed that these patients have a defect in G s signaling. Functional studies in membranes (304,338) and whole cells (339) confirmed that these patients have a defect in G s signaling.…”
Section: The Role Of Inactivating G S ␣ Mutations and G S ␣ Imprinmentioning
confidence: 94%
“…Biochemical assays that measure hormone signaling after reconstitution of patient cell membranes with membranes that totally lack G s (cycϪ) demonstrated that in PHPIA functional G s activity is decreased by approximately 50% in membranes from various cell types, including erythrocytes, fibroblasts, platelets, lymphocytes, and kidney (288,(325)(326)(327)(328)(329)(330)(331)(332)(333)(334)(335). Functional studies in membranes (304,338) and whole cells (339) confirmed that these patients have a defect in G s signaling. Functional studies in membranes (304,338) and whole cells (339) confirmed that these patients have a defect in G s signaling.…”
Section: The Role Of Inactivating G S ␣ Mutations and G S ␣ Imprinmentioning
confidence: 94%
“…This may result from insufficient duration of fetal cortisol exposure or failure to reach a threshold level necessary to induce changes in the myocardium. Alternatively, gestation‐dependent effects may be cortisol‐independent or may require concomitant activity in additional endocrine systems, such as the thyroid axis (Heinsimer et al 1984; Pracyk & Slotkin, 1991, 1992; Birk et al 1992). It is of interest that, although in the current study fetal cortisol infusion failed to have a significant effect on chronotropic and inotropic responses to carbachol or isoprenaline, it did increase basal LV, but not RV, developed pressure.…”
Section: Discussionmentioning
confidence: 99%